Robert Worth Bingham papers - Bingham, Robert Worth, 1871-1937.
Correspondence, diaries, speeches, financial records, appointment books, clippings, scrapbooks, and other papers relating primarily to Bingham's service as ambassador to Great Britain. Subjects include war debt negotiations; Monetary and Economic Conference, London, Eng., 1933; London Naval Conference, 1935-1936; invasion of Ethiopia (Italo-Ethiopian War, 1935-1936); the gold standard and other monetary and tariff issues; disarmament; world politics including the rising influence of Japan; political leaders including Neville Chamberlain, Adolf Hitler, Benito Mussolini, and Franklin D. Roosevelt; and Bingham's social activities in England. Other subjects include the operation and policies of Bingham's newspapers, the Louisville Courier-Journal and the Louisville Times; national and Kentucky politics; education, penal and charitable institutions, and roads in Kentucky; tobacco cooperatives; agriculture; and personal and family matters.
Correspondents include John Jacob Astor; Ray Atherton; Stanley Baldwin, Earl Baldwin; Alben William Barkley; Bernard M. Baruch; John Crepps Wickliffe Beckham; Ulric Bell; Barry Bingham; Carrie Chapman Catt; Calvin Coolidge; Josephus Daniels; Norman H. Davis; Anthony Eden, Earl of Avon; Mark Etheridge; James A. Farley; Credo Fitch Harris; Roland Hayes; Herbert Hoover; Edward Mandell House; Cordell Hull; Joseph P. Kennedy; Arthur Krock; Emanuel Levi; Charles A. Lindbergh; David Lloyd George; Breckinridge Long; Henry Robinson Luce; James Ramsay MacDonald; Lincoln MacVeagh; Jan Masaryk; Eugene Meyer; Margaret Mitchell; Henry Morgenthau (1856-1946); Adolph S. Ochs; John D. Rockefeller (1874-1960); Eleanor Roosevelt; Franklin D. Roosevelt; Daniel C. Roper; Cornelius Vanderbilt (1898-1974); Henry A. Wallace; Tom Wallace; Thomas John Watson; Henry Watterson; and Woodrow Wilson.
Library of Congress Prints and Photographs Division.
Library of Congress Music Division.
Diplomat, lawyer, and newspaper publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Astor, John Jacob, -- 1886- -- Correspondence; Atherton, Ray, -- 1883-1960 -- Correspondence; Baldwin, Stanley Baldwin, -- Earl, -- 1867-1947 -- Correspondence; Barkley, Alben William, -- 1877-1956 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Beckham, John Crepps Wickliffe, -- 1869-1940 -- Correspondence; Bell, Ulric, -- 1891-1960 -- Correspondence; Bingham, Barry, -- 1906-1988 -- Correspondence; Catt, Carrie Chapman, -- 1859-1947 -- Correspondence; Chamberlain, Neville, -- 1869-1940.; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, Norman H. -- 1878-1944 -- Correspondence; Eden, Anthony, -- Earl of Avon, -- 1897-1977 -- Correspondence; Etheridge, Mark -- Correspondence; Farley, James A. -- 1888-1976 -- Correspondence; Harris, Credo Fitch, -- 1874-1953 -- Correspondence; Hayes, Roland, -- 1887-1977 -- Correspondence; Hitler, Adolf, -- 1889-1945.; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Krock, Arthur, -- 1886- -- Correspondence; Levi, Emanuel -- Correspondence; Lindbergh, Charles A. -- 1902-1974 -- Correspondence; Lloyd George, David, -- 1863-1945 -- Correspondence; Long, Breckinridge, -- 1881-1958 -- Correspondence; Luce, Henry Robinson, -- 1898-1967 -- Correspondence; MacDonald, James Ramsay, -- 1866-1937 -- Correspondence; MacVeagh, Lincoln, -- 1890-1972 -- Correspondence; Masaryk, Jan, -- 1886-1948 -- Correspondence; Meyer, Eugene, -- 1875-1959 -- Correspondence; Mitchell, Margaret, -- 1900-1949 -- Correspondence; Morgenthau, Henry, -- 1891-1967 -- Correspondence; Mussolini, Benito, -- 1883-1945.; Ochs, Adolph S. -- 1858-1935 -- Correspondence; Rockefeller, John D., -- Jr. -- 1874-1960 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Vanderbilt, Cornelius, -- 1898- -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Wallace, Tom, -- 1874-1961 -- Correspondence; Watson, Thomas John, -- 1874-1956 -- Correspondence; Watterson, Henry, -- 1840-1921 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Bingham family; Louisville courier-journal.; Louisville times; Agriculture; American newspapers -- Kentucky; Charities -- Kentucky; Diplomatic and consular service, American -- Great Britain; Disarmament; Gold standard; Italo-Ethiopian War, 1935-1936.; Money; Prisons -- Kentucky